Covid 19 pandemic on the growth of the entrepreneurship society in Indonesian community - Mahfud, Imam; Arifin, Mohamad Zaenal; Ulpah, Mariya (Priviet Social Sciences Journal, 2022)
The COVID-19 pandemic has given birth to many positive things in our society, especially in building a people's economy, or the emergence of many new MSMEs which have become a new change in the behavior of the Indonesian people. This study uses a literature study by conducting descriptive analysis by combining existing data and information in order to obtain scientific conclusions. The outbreak of the COVID-19 virus means society needs to reengage and fundamentally adapt to Entrepreneurship, and is well suited to taking a crisis perspective that can offer advancements to other streams of innovation including business and sociology. Entrepreneurial action incorporates a powerful mindset that can help society bounce back from the crisis. The COVID-19 pandemic has led to new behavior towards the community, especially those affected by COVID-19, especially in terms of the economy, so that people can adapt more quickly to be more productive and have high competitiveness, thus giving birth to a community culture that has an entrepreneurial spirit.